Systematic Literature Review and Network Meta-Analysis of Clinical Efficacy and Safety of Topical Treatments for Patients with Atopic Dermatitis - Hiroyuki Murota; Takeshi Nakahara; Xinyu Wang; Miyuki Matsukawa; Hiroe Takeda; Tomohiro Kondo; Kentaro Yamato (Dermatology and Therapy)
Abstract Introduction In Japan, atopic dermatitis (AD) is one of the most common skin diseases, with the number of patients steadily increasing in recent years. Thus, it is crucial to assess the efficacy and safety of currently existing and recently introduced new treatments. Methods A systematic literature review (SLR) and network meta-analysis (NMA) was conducted to evaluate the clinical efficacy and safety of existing standard topical therapies and new topical treatments for AD. Medline, Embase, Cochrane, and ICHUSHI were used to select studies. The Eczema Area and Severity Index (EASI) score and Investigator Global Assessment (IGA) score were efficacy outcomes, whereas any serious adverse events (AEs), acne, and skin infections were safety outcomes. A Bayesian multiple treatment NMA with fixed effects was performed. Odds ratio with 95% credible interval (CrI) was used to compare the outcomes of different topical medications including placebo for AD. Results A total of 11 randomised controlled trials (RCTs) conducted in adult patients with varying degrees of AD severity were selected for NMA. The systematic review showed improvement in EASI scores with difamilast 0.3% and 1% and tacrolimus 0.1% as well as in IGA score success rates with difamilast 1%, delgocitinib 3%, and tacrolimus 0.1%. According to NMA, at week 4, difamilast 1% twice daily (BID) showed a significant improvement in the IGA score and percent EASI score change from baseline versus placebo; however, compared to other comparators, point estimates numerically favoured difamilast 1% but were not statistically significant. Difamilast 1% BID showed a significantly lower incidence of acne than delgocitinib 0.3% BID. There was no statistically significant difference in the incidence of serious AEs, acne, and skin infections compared to placebo or other comparators. Conclusion This study establishes the efficacy and safety of current topical treatment options and recently marketed delgocitinib and difamilast ointments for AD in Japan.